Correlating chlorine-induced changes in mechanical properties to performance in polyamide-based thin film composite membranes - Lee, Jung-Hyun; Chung, Jun Young; Chan, Edwin P.; Stafford, Christopher M. (ELSEVIER SCIENCE BV, 2013)
In this study, chlorine-induced structural changes of fully-aromatic and semi-aromatic polyamide (PA) active layers used in reverse osmosis (RO) and nanofiltration (NF) membranes, respectively, were investigated by a combination of mechanical property measurements and performance studies. Our results indicated that chlorination causes quite different changes in mechanical properties of the active layer depending on the chemical nature of the PA, as identified by increased brittleness for a fully-aromatic PA and improved ductility for a semi-aromatic PA. Moreover, the results revealed that the mechanical responses of the PA active layers after chlorine exposure correlate to the overall membrane performance. A significant increase in water flux and a large decrease in salt rejection were observed for the RO membrane after chlorination, which can be ascribed to the increased fragility and resultant defects of the oxidized fully-aromatic PA network. In sharp contrast, the chlorination of the NE membrane resulted in a slightly reduced water flux accompanied with improved salt rejection, suggestive of structural compaction and densification of the semi-aromatic PA network induced by enhanced chain flexibility. We contend that our thin film measurement methodology provides key mechanical property measurements of the PA active layer and begins to bridge the gap between compositional chemical analyses and membrane performance measurements. Published by Elsevier B.V.
Keywords: REVERSE-OSMOSIS MEMBRANE; HYDROGEN-BONDING BEHAVIOR; HYPOCHLORITE DEGRADATION; NF MEMBRANES; NANOFILTRATION MEMBRANES; WATER-PURIFICATION; LAYER; RO; HETEROGENEITY; DESALINATION